2006
DOI: 10.1001/archpsyc.63.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Neurologic Compromise as a Vulnerability Factor for Combat-Related Posttraumatic Stress Disorder

Abstract: These results replicate previous findings of increased NSSs in Vietnam combat veterans with PTSD. Furthermore, results from their combat-unexposed identical co-twins support the conclusion that subtle neurologic dysfunction in PTSD is not acquired along with the trauma or PTSD but rather represents an antecedent familial vulnerability factor for developing chronic PTSD on exposure to a traumatic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 26 publications
(44 reference statements)
3
63
0
Order By: Relevance
“…86 Similarly, PTSD, which is highly co-morbid with depression, has been proposed based on a variety of data, to be due in part to a deficit in extinction of fear. [29][30][31][32] A recently published study also demonstrates that there may be spatial memory deficits, for example copying figures and other similar neurological soft signs, in twin subjects with PTSD compared to their identical twin without PTSD, 87 consistent with the correlations seen here between spatial memory performance in the water maze and extinction of fear.…”
Section: Extinction Deficit With Hippocampal Bdnf Deletionssupporting
confidence: 83%
“…86 Similarly, PTSD, which is highly co-morbid with depression, has been proposed based on a variety of data, to be due in part to a deficit in extinction of fear. [29][30][31][32] A recently published study also demonstrates that there may be spatial memory deficits, for example copying figures and other similar neurological soft signs, in twin subjects with PTSD compared to their identical twin without PTSD, 87 consistent with the correlations seen here between spatial memory performance in the water maze and extinction of fear.…”
Section: Extinction Deficit With Hippocampal Bdnf Deletionssupporting
confidence: 83%
“…Monozygotic twin studies of Vietnam veterans suggest that subtle ("soft") NDs, which likely resulted from mild inherited alterations in cerebral function, may predispose to PTSD [50]. The 45 neurological signs measured in the Vietnam veterans were similar to the elements of the neurological examination performed in this study.…”
Section: Variablesupporting
confidence: 66%
“…Monozygotic twins were studied where one twin was in combat and the other not. Among twins pairs where the twin who had been in combat developed PTSD, both twins had a higher prevalence of neurological soft signs [50] or gray matter abnormalities in the right hippocampus, pregenual anterior cingulate cortex, and left and right insular cortex [51] than the twin pairs where the combat-exposed twin did not have PTSD. The presence of similar patterns of NDs among both of the monozygotic twins suggests that the observed NDs were genetic in origin.…”
Section: Variablementioning
confidence: 89%
“…There is a significant genetic component to risk for PTSD (Kendler, 2001), as well as neurological abnormalities in unaffected probands that are suggestive of antecedent genetic or familial risk factors (Gurvits et al, 2006). Functional neuroimaging studies have identified hyperactivity of the amygdala as a neural correlate for the clinical symptoms seen in PTSD Shin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%